THE EDUCATIONAL GAME-BASED EMODUL: IS IT EFFECTIVE AND SOLUTION TO THE MERDEKA CURRICULUM? - Munir, Syahrul; Haryono , Agung; Rokhmani, Lisa; Inayati, Roufah; Anisya, Anisya; Masruro , Umi; Fitrianti, Wahyu (International Education Trend Issues, 2023)
Various innovations in implementing learning activities are efforts to support the implementation of the Merdeka curriculum. One of the innovations was carried out by developing the Android-based " Money Adventure E-module " in economic learning. The Money Adventure e-module is expected to provide a pleasant learning experience and overcome difficulties in understanding money and payment instruments, as well as improving student learning outcomes. This research aims to develop Android-based e-modules as effective learning materials in economics learning to support the implementation of the Merdeka curriculum at SMAN 1 Tulungagung. The development of this e-module was carried out using the 4D model from Thiagrajan, which was followed by testing the effectiveness of the e-module in improving student learning outcomes, through quasi-experimental activities with a nonequivalent control group design model, in class X-2 as an experimental class and class X - 3 as a control class. The material expert validation test results were 91.67 % with very good criteria, while the material and learning media expert validation results were 88.33% with good criteria. The Money Adventure e-module has proven effective in improving student learning outcomes in learning economics regarding money and payment instruments. This can be seen from the average post-test score for the experimental class (88.19 ) which is higher than the control class (65.83). This is also reinforced by the results of the average difference test for the experimental class and the control class which shows that there is a significant difference between the learning outcomes of the experimental class and the control class